Prebiotic and Probiotics Supplementation used in Animal Nutrition Have Their Effects on Gut Health and Animal Performance - Usman, Muhammad; Noor, Maaz; Ahmed, Umair; Khan, Ayesha; Ahmad, Sohail; Khan, Areej; Rehman, Abdul; Kazmi, Syeda Umm e Farwa; Arshad, Uzair; Abdullah, Obaid Muhammad (Indus Journal of Bioscience Research, 2025)
The increasing demand for efficient and sustainable animal production has led to investigating alternative nutritional strategies, including prebiotics and probiotics. This study examined the synergistic effects of prebiotic and probiotic supplementation on gastrointestinal health and performance in livestock species, encompassing chicken, swine, and cattle. A randomized controlled trial was executed over a 12-week duration with 150 chickens, 100 pigs, and 60 cattle at UVAS, Lahore, who were allocated into three groups: control (typical food), probiotic supplementation, and a combination of prebiotic and probiotic supplementation. Data on growth rate, feed conversion ratio (FCR), gut microbiota composition, cytokine levels (TNF-alpha, IL-6), intestinal permeability, and illness prevalence were gathered. Statistical analysis, encompassing ANOVA, t-tests, and regression models, was employed to evaluate the impact of supplementation. The findings indicated that the Probiotic and Combination groups showed substantial enhancements in growth rate and Feed Conversion Ratio (FCR) relative to the Control group. The Combination group exhibited the most significant enhancement in gut microbial diversity and the most substantial decrease in intestinal permeability. Furthermore, both experimental cohorts exhibited diminished levels of inflammatory cytokines and a decreased prevalence of gastrointestinal disorders, with the Combination group demonstrating the most favorable outcomes. The data indicates that concurrently administering prebiotics and probiotics can enhance livestock growth efficiency, gastrointestinal health, and disease resistance. This study highlights the benefits of prebiotic and probiotic supplementation in livestock, improving gut health, growth rate, feed conversion, and immunity. The combination group showed the most significant improvements, supporting a synergistic effect. Future research should address long-term impacts, dose responses, and economic viability to enhance sustainable livestock production.